Entwining ecosystem services, Land Use Change and human well-being by nitrogen flows. (25th July 2021) - Dong, Xiaobin; Ren, Jiahui; Zhang, Peng; Jin, Yan; Liu, Ranran; Wang, Xue-Chao; Lee, Chew Tin; Klemeš, Jiří Jaromír
Abstract: Identifying the linkage among Land Use Change, Ecosystem Services, and Human Well-Being (LUC-ES-HW) is essential for a clearer understanding of the interactive mechanism behind the natural-social system. There are limited studies designed for exploring the LUC-ES-HW nexus from the material flow perspective. This study explores the LUC-ES-HW nexus in terms of nitrogen flows, identifying the ecological and environmental process. A LUC-ES-HW system assessment framework based on nitrogen flows is established in this work, taking the Manas River Basin as a case study. The results showed that Land-Use Change (LUC) had a significant impact on the environmental performance and Ecosystem Services (ES); consequently, exert great influence on Human Well-Being (HW). This study can contribute to a better understanding of LUC-ES-HW Nexus, and provide a reference for future relevant studies.